Genetic Determinants of Biomass in C4 Crops: Molecular and Agronomic Approaches to Increase Biomass for Biofuels - Ain, Noor-ul-; Haider, Fasih Ullah; Fatima, Mahpara; Habiba,; Zhou, Yongmei; Ming, Ray (Frontiers in Plant Science, 2022)
Bio-based fuels have become popular being efficient, cost-effective, and eco-friendly alternatives to fossil fuels. Among plant sources exploited as feedstocks, C4 grasses such as sugarcane, maize, sorghum, and miscanthus are highly resourceful in converting solar energy into chemical energy. For a sustainable and reliable supply of feedstocks for biofuels, we expect dedicated bioenergy crops to produce high biomass using minimum input resources. In recent years, molecular and genetic advancements identified various factors regulating growth, biomass accumulation, and assimilate partitioning. Here, we reviewed genes involved in cell cycle regulation, hormone dynamics, and cell wall biosynthesis, and important transcription factors responsible for biomass increase. Also, environmental components interacting with genetic controls modulate plant biomass by modifying gene expression in multiple interacting pathways. Finally, we discussed recent progress using hybridization and genome editing techniques to improve biomass yield in C4 grasses. This review provides an overview of genes and environmental factors controlling biomass yield in C4 biofuel crops which can help to discover and design bioenergy crops adapting to changing climate conditions.